Pengaruh Perputaran Piutang Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Hotnida R Simanullang; Halomoan S Sihombing; Hendrik ES Samosir (Politeknik Ganesha Medan, 2024)
This study aims to determine the effect of accounts receivable turnover and inventory turnover on profitability in food and beverage subsector companies listed on the IDX (Indonesia Stock Exchange) for the 2020-2022 period. The population in this study is food and beverage subsector companies listed on the IDX for the 2020-2022 period. The sampling technique in this study was carried out by purposive sampling so that 23 companies were obtained. The type of data used in this study is secondary data and the data collection method used is the documentation method. The data analysis technique used is descriptive statistical analysis of variables and classical assumption tests, which in calculating using application assistance in the SPSS version 26 program. From the results of hypothesis testing, it can be concluded that accounts receivable turnover has no effect on profitability in food and beverage subsector companies listed on the IDX for the 2020-2022 period and inventory turnover also has no effect on profitability in food and beverage subsector companies listed on the IDX for the 2020-2022 period or it can also be concluded that the first hypothesis and second hypothesis are rejected. This is shown through the results of the t-test which shows a significant relationship to variables with a significance level of 5%.